Clearance of von Willebrand factor - Denis, Cécile V.; Christophe, Olivier D.; Oortwijn, Beatrijs D.; Lenting, Peter J. (Thrombosis and Haemostasis, 2008)
The life cycle of von Willebrand factor (VWF) comprises a number of distinct steps, ranging from the controlled expression of theVWF gene in endothelial cells and megakaryocytes to the removal of VWF from the circulation. The various aspects of VWF clearance have been the objects of intense research in the last few years, stimulated by observations thatVWF clearance is a relatively common component of the pathogenesis of type 1 von Willebrand disease (VWD). Moreover, improving the survival of VWF is now considered as a viable therapeutic strategy to prolong the half-life of factor VIII in order to optimise treatment of haemophilia A. The present review aims to provide an overview of recent findings with regard to the molecular basis of VWF clearance. A number of parameters have been identified that influence VWF clearance, including its glycosylation profile and a number of VWF missense mutations. In addition, in-vivo studies have been used to identify cells that contribute to the catabolism of VWF, providing a starting point for the identification of receptors that mediate the cellular uptake ofVWF.Finally, we discuss recent data describing chemically modification of VWF as an approach to prolong the half-life of the VWF/FVIII complex.
Keywords: VonWillebrand factor; factorVIII; animal models; vonWillebrand disease